Improving Adolescent Mental Health Care in Indonesia: A Systematic Review of Electronic Medical Record Implementation - Sulistyawati, Anggraini Budi; Susilowati, Ari (International Journal of Statistics in Medical Research, 2026)
Background: Adolescent mental health disorders represent a significant global public health challenge, with low rates of detection and treatment in many settings. Electronic Medical Records (EMRs) are increasingly recognized as pivotal tools for improving the integration of validated screening, supporting clinical decision-making, and enabling continuous quality monitoring in mental health care. However, the specific utility, effectiveness, and implementation challenges of EMRs in developing nations, particularly in Southeast Asia, such as Indonesia, remain underexplored. Methods: An extensive search was conducted across international databases (e.g., PubMed, ScienceDirect, Scopus) and relevant regional databases (e.g., Garuda, SINTA) to capture studies published in both English and Bahasa Indonesia. Search terms will encompass ’electronic medical records,’ ’EMR,’ ’EHR,’ ’adolescent,’ ’youth,’ ’mental health,’ ’depression,’ ’anxiety,’ ’suicide,’ and ’Indonesia.’ Inclusion criteria will focus on studies involving adolescents (aged 10-24 years) and EMR-based mental health interventions. Two independent reviewers will conduct title, abstract, and full-text screening. Data extraction will concentrate on study design, population characteristics, EMR functionalities, clinical outcomes, patient engagement, provider workflow, implementation barriers, and reported disparities. A qualitative synthesis will pooled effects and quantify EMR impact on clinical outcomes context-specific recommendations for Indonesia. Results: This review aims to provide a robust overview of EMR applications in adolescent mental health in the Indonesian context. Globally, EMR integration consistently improved screening efficiency, increasing rates by 20–30 percentage points compared to paper-based systems. Provider training amplified these effects, with odds ratios exceeding 40 for screening uptake and relative risks of 2.7 for new diagnoses. Validation studies confirmed diagnostic reliability, reporting positive predictive values up to 100% for lifetime psychiatric disorders. Conclusion: Large-scale surveillance networks revealed rising prevalence of anxiety, eating disorders, and suicidality, with detection occurring at younger ages. These findings highlight EMRs as not only efficiency tools but urgent safeguards against systemic fragility in Indonesia.